An Efficient Jamming Node Avoid Secure Routing In Internet of Things - Selvi, E; Renuka, K (International Journal of Computer Sciences and Engineering, 2018)
The shared wireless medium, wireless networks are vulnerable to jamming attacks. These types of attacks can easily be accomplished by an adversary by either bypassing MAC layer protocol or by emitting RF signals. The failure of data transmission in internet of things is due to corruption of packets by jammers. In existing no of defense techniques have been proposed in recent years to deal with these jammer attacks. However, each defense technique is suitable for only a limited network range and consumption energy. The propose jamming detection algorithm based on two problem solving, first one is to improve the energy efficient routing based on power allocation and second one avoids the jamming node using ecliptic curve cryptography to route the secure packet between source to destination. The simulation result shows the better throughput and delay minimization compare with existing routing algorithms.